Escherichia coli Ribosome-Associated Protein SRA, Whose Copy Number Increases during Stationary Phase - Izutsu, Kaori (American Society for Microbiology, 2001)
Protein D has previously been demonstrated to be associated with Escherichia coli ribosomes by the radical-free and highly reducing method of two-dimensional polyacrylamide gel electrophoresis. In this study, we show that protein D is exclusively present in the 30S ribosomal subunit and that its gene is located at 33.6 min on the E. coli genetic map, between ompC and sfcA. The gene consists of 45 codons, coding for a protein of 5,096 Da. The copy number of protein D per ribosomal particle varied during growth and increased from 0.1 in the exponential phase to 0.4 in the stationary phase. For these reasons, protein D was named SRA (stationary-phase-induced ribosome-associated) protein and its gene was named sra. The amount of SRA protein within the cell was found to be controlled mainly at the transcriptional level: its transcription increased rapidly upon entry into the stationary phase and was partly dependent on an alternative sigma factor (sigma S). In addition, global regulators, such as factor inversion stimulation (FIS), integration host factor (IHF), cyclic AMP, and ppGpp, were found to play a role either directly or indirectly in the transcription of sra in the stationary phase.